Depression among older adults in Iceland : examining the Geriatric Depression Scale (GDS) - Þóra Kristín Flygenring 1990- (2016)
Background/aims: Depression among the elderly in Iceland has not been studied extensively. Therefore, the aims of the study were to assess depression and determine risk factors in this group, and examine certain psychometric properties of the Geriatric Depression Scale (GDS). Method: Participants were 300 senior citizens between the ages of 65-100. Participants filled out GDS and other subjective self-assessment scales (UCLA loneliness scale, Memory Complaints Questionnaire). They also completed several cognitive tests (Mini Mental State Examination, Modified Mini Mental State, Mattis Dementia Rating Scale). Results: Around 12% of participants (8.3% of males and 13.5% of females) had a score of 11 or more on GDS, which is an indication of depression. GDS showed acceptable internal reliability and factor analysis revealed four factors. Significant risk factors for depression included being female, being older, and being lonely. Married people had fewer depression symptoms than others, but after controlling for the other risk factors, marital status did not predict depression scores. Those who had worse results on cognitive tests and had worse self-reported memory had more depressive symptoms than others. Residence and education level were not related to depression. Conclusions: The results suggest that depression symptoms are fairly common among older people, but previous studies have suggested that depression might be under-diagnosed in this group. It is therefore imperative that health care personnel are conscious of the risk of depression when they assess the physical and psychological state of elderly patients. The Icelandic version of GDS could be used to this purpose. Keywords: depression, Geriatric Depression Scale, the elderly, Iceland, risk factors Bakgrunnur/tilgangur rannsóknar: Þunglyndi meðal aldraðra hefur lítið verið rannsakað á Íslandi. Markmið rannsóknarinnar voru annars vegar að meta þunglyndi og greina áhættuþætti þunglyndis í þessum hópi og hins vegar að kanna ákveðna próffræðilega ...